Rhizophagus irregularis MUCL 41833 Improves Phosphorus Uptake and Water Use Efficiency in Maize Plants During Recovery From Drought Stress - Le Pioufle, Olivia; Ganoudi, Matike; Calonne-Salmon, Maryline; Ben Dhaou, Fatma; Declerck, Stéphane (Frontiers in Plant Science, 2019)
Irregular precipitations are likely to affect maize production in the future. Arbuscular mycorrhizal fungi (AMF) have been reported to increase maize resistance to drought, but their role on the short-term inorganic phosphorus (Pi) uptake, leaf gas exchange parameters and water content during recovery after drought remains poorly understood. Here, we investigated these parameters in maize plants colonized or not by Rhizophagus irregularis MUCL 41833. The mycorrhizal (M) and non-mycorrhizal (NM) plants were grown for a 3-week period in a circulatory semi-hydroponic cultivation system and were submitted to well-, moderately- or poorly-watered conditions (WW, MW and PW, respectively), the two latter conditions corresponding to moderate and severe droughts. The plants were then watered at field capacity for 42 h with a Pi impoverished Hoagland nutrient solution and the dynamic of Pi depletion in the nutrient solution, corresponding to Pi uptake/immobilization by the maize-AMF associates, was evaluated at 0, 9, 21 and 42 h. The CO2 assimilation rate (A), stomatal conductance (gs), transpiration (E) and instantaneous water use efficiency (WUEi) were also assessed at 0 and 42 h of circulation. Plant biomass, plant water content, phosphorus concentration and content, and leaf relative water content were evaluated at harvest. During recovery, Pi uptake was significantly higher in M versus NM plants whatever the water regime (WR) applied before recovery. AMF did not affect leaf gas exchange parameters before recovery but modulated gs and E, and improved WUEi after 42 h of recovery. At harvest, no significant difference in dry biomass was found between M and NM plants but shoot fresh weight was significantly higher in M plants. This resulted in an increased shoot water content in M plants grown in the MW and PW treatments. Surprisingly, leaf relative water content was significantly lower in M plants when compared with NM plants. Finally, P content and concentration were significantly higher in roots but not in shoots of M plants. Our results suggested that AMF can play a role in drought resistance of maize plants by increasing the Pi uptake and WUEi during recovery after drought stress.